Stevens in Leseland, the East German “Land of Readers” - Akansu, Eyk (Wallace Stevens Journal, 2024)
It remains to be seen whether the GDR as a Leseland was more a wish of cultural policy than a reality, but it did produce some remarkable editorial achievements. These include the Weiße Reihe of twentieth-century poetry from around the world. The fact that Wallace Stevens did not appear in it until more than twenty years after his appearance in the West German edition, from which numerous translations were taken, may have banal causes or indicate a delayed hospitality. In any case, the censorship reports show how hard the experts tried to read both the author and the poems through the lens of socialist realism, which over time had become an empty phrase for a concept that remained vali
Keywords: East Germany; Menschen; aus Worten gemacht; Volk und Welt; Weiße Reihe; Der Planet auf dem Tisch; Hauptverwaltung Verlage und Buchhandel; Censorship